THE INFLUENCE OF CONSUMER BEHAVIOR ON THE PURCHASE DECISION OF HYDROPONIC VEGETABLES IN PUCCAN HYDROPONIC, BLITAR CITY: PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SAYUR HIDROPONIK DI PUCCAN HIDROPONIK KOTA BLITAR - Tri Kurniastuti; Yeyen Nurindah Sari (Universitas Islam Balitar, 2023)
The research aims to determine the effect of consumer behavior on purchasing decisions for hydroponic vegetables at Puccan Hydroponics. The results of the analysis show that there are 4 factors considered, namely Product, Price, Place, and Promotion on Purchase Decision using multiple linear regression analysis. The population is hydroponic vegetable consumers at Puccan Hydroponics with a total sample of 30 respondents. The sampling technique in this study was the accidental sampling method. Based on the research results, from the results of the F test it can be seen that the variables Product, Price, Place, and Promotion together have a significant effect on the Purchase Decision variable. From the results of the T test it can be seen that the price variable partially influences purchasing decisions, while the product, place, and Promotion does not partially influence the Purchase Decision. From the test results of the coefficient of determination, Product, Price, Distribution, and Promotion variables contribute 90% to the Purchasing Decision variable. While 10% is influenced by other factors.